Low-dose brachytherapy for early stage penile cancer: a 20-year single-institution study (73 patients). Issue 1 (December 2016) - Cordoba, Abel; Escande, Alexandre; Lopez, Stephanie; Mortier, Laurent; Mirabel, Xavier; Coche-Déqueant, Bernard; Lartigau, Eric
Abstract Purpose/objectives The aim of this study is to analyze the results of exclusive interstitial brachytherapy (IBT) as a conservative approach in the treatment of penile cancer confined to the glans or the shaft with long-term follow-up in a single institution. Materials/methods Between July 1992 and November 2013, 73 consecutive patients with non-metastatic invasive penile cancer were treated by Low dose rate (LDR) IBT in our institution. The localization of the primary lesion was glands in 67 patients (91.8 %) and shaft in 6 patients (8.2 %). All 73 patients presented with squamous cell carcinoma with grades of differentiation as follows: 34 patients with grade 1 (44.7 %), 9 patients with grade 2 (11.8 %), 9 patients with grade 3 (11.8 %) and 21 patients unknown (28.8 %). Six patients (7.8 %) presented with in situ carcinoma, 55 patients (75, 3 %) presented with T1, 11 patients (15 %) presented with T2, and one patient (1.3 %) presented with Tx. Inguinal nodal dissection was performed in 29 patients (38.2 %); 13 patients (17.8 %) presented with histologically confirmed positive ganglion. After circumcision, IBT was performed using a hypodermic needle. The median dose delivered was 60 Gy (range, 40 to 70 Gy). The median activity of the iridium-192 wire was 1.12 mCi/cm, and the median reference isodose rate was 0.4 Gy/h (range, 0.2–1.2). Patients with histological inguinal metastases received external beam radiotherapy to the selected inguinal affected area with a median dose of 45 Gy (30–55 Gy). Results The median follow-up time was 51.8 months (range 34.4 to 68.7). The 5-year overall survival was 82.0 %, with eight deaths from cancer and five non-cancer-related deaths. Disease-specific survival was 91.4 %, relapse-free survival was 64.4 %, and local relapse-free survival as 74 %. Total or partial penile preservation was 87.9 % at 5-years. Complications rates at 5 years were 6.6 % urethral stenosis (five patients), two patients (2.6 %) with pain related to sexual intercourse and four patients (5.3 %) with dysuria grade 2. Five patients (6.8 %) required penile amputation for necrosis. Conclusions IBT provides good local control with organ preservation, excellent tolerance and low complication rates in early-stage penile cancers.